Profilin-A master coordinator of actin and microtubule organization in mammalian cells - Karlsson, Roger; Dráber, Pavel (Journal of cellular physiology, 2021)
The last two decades have witnessed a tremendous increase in cell biology data. Not least is this true for studies of the dynamic organization of the microfilament and microtubule systems in animal cells where analyses of the molecular components and their interaction patterns have deepened our understanding of these complex force-generating machineries. Previous observations of a molecular cross-talk between the two systems have now led to the realization of the existence of several intricate mechanisms operating to maintain their coordinated cellular organization. In this short review, we relate to this development by discussing new results concerning the function of the actin regulator profilin 1 as a control component of microfilament-microtubule cross-talk.
Keywords: Microtubules; signální transdukce; mikrofilamenta; Actin Cytoskeleton; Profilins; Actins; Animals; lidé; profiliny; Humans; zvířata; mikrotubuly; aktiny; Signal Transduction